A Matter of Time? Measuring Effects of Public Schooling Expansions on Families' Constraint - Chloe R. Gibbs; Jocelyn Wikle; Riley Wilson (CESifo GmbH, 2024)
As women increasingly entered the labor force throughout the late 20th century, the challenges of balancing work and family came to the forefront. We leverage pronounced changes in the availability of public schooling for young children—through duration expansions to the kindergarten day—to better understand mothers' and families' constraints. We first show that mothers of children in full-day kindergarten spend significantly more time at work, less time with their children, less time performing household duties, and less time commuting with their children in the middle of the day relative to mothers with half-day kindergarteners. Exploiting full-day kindergarten variation across place and time from 1992 through 2022, combined with the narrow age targeting of kindergarten, we document the impact of full-day kindergarten access on parental labor supply, family childcare costs, and children's subsequent academic outcomes. Our estimates of the maternal employment effects imply that full-day kindergarten expansions were responsible for as much as 24 percent of the growth in employment of mothers with kindergarten-aged children in this time frame.
Keywords: H75; I28; J13; J22; 330; public schooling; kindergarten; maternal labor supply